‘Love, Love not’—a discovery of study engagement at higher education and the factors involved - Nguyen, Trang Thi Nhu; Bui, Thai Thi Hong; Nguyen, Lan Thi; Dao, Hang Thuy; Nguyen, Nguyen Lan; Mai, Hanh Tuyet; Nguyen, Ha Thi Thu (Frontiers in Education, 2024)
Taking that higher education is career-oriented, this study examines how Vietnamese undergraduate students engage with their study and how the factors related to the training program and occupation’s prospects contribute to students’ engagement with their study. The study applies a mixed-method approach. Self-administered questionnaire survey is used to collect data from 973 Vietnamese undergraduate students, of which 48.2% are social work students and 51.8% are non-social work students. In addition, the study conducts 27 semi-structured interviews with students and lecturers to explore their perspective and experiences with regard to students’ study engagement and the factors involved. The results show that social work students are more engaged with their study than non-social work students, even though they feel more worried about job opportunity and income. Approximately one-third of social work students consider not to pursue social work profession when they graduate mostly because they believe that working in social work cannot provide them the income they need for their living. However, the results also show that students’ satisfaction/dissatisfaction with income in their field was not statistically related to their study engagement. Instead, feeling of personal growth, opportunity to perform personal ability, sense of significance, convenient access to study materials and activities, and feeling proud of their school and lecturers’ prestige are found positively associated with students’ level of study engagement. The study hence provides some recommendations for educators to strengthen students’ study engagement at higher education level.